Residue fractionation and decomposition: the significance of the active fraction - Vanlauwe, Bernard; Dendooven, Luc; Merckx, Roel (1994)
This paper describes an incubation experiment with homogeneously 14C labeled maize-straw and its insoluble fraction. The role of the soluble fraction in the decomposition process was assessed, using three independently measured characteristics: (1) fractionation of the maize-straw, resulting in kinetically different fractions; (2) microbial biomass C and its 14C activity determined by a fumigation extraction method, and (3) the 14C activity of the released CO2-C. The fumigation extraction method was proved to be useful from 9 days after the application of the maize-straw onwards. The fractionation method yielded a soluble (48%), a (hemi) cellulosic (47%), and a lignin fraction (1%). Nine days after addition of either the complete residue or its insoluble fraction, the microbial biomass C increased from 53 to 337 and 217 mg C kg-1 dry soil, respectively. Similar values were maintained up to day 40. The large increase in microbial activity was accompanied by a N-immobilization of 65 and 29 mg N Kg-1 dry soil for the maize-straw treatment and its insoluble fraction, respectively, resulting in biomass C/N values of 5.5 and 5.6 A genuine priming effect (10 and 7% of the total CO2-C production) on the mineralization of native soil organic C was caused by an increase in decomposition of the native C rather than by an increase in turnover of the microbial biomass in the soil amended with maize straw. The soluble fraction caused a 'priming effect' on the decomposition of the less decomposable cell-wall fraction. Calculations by nonlinear regression confirmed this observation.